The proportion of first-year males in Swedish populations of Black Redstart Phoenicurus ochruros - Andersson, Reino (Ornis Svecica, 2022)
The Black Redstart Phoenicurus ochruros immigrated to Sweden around the turn of the last century, however the great wave of expansion took place from the late 1940s until the 1980s. The early expansion was considered to mainly comprise inexperienced young birds, which extended their spring migration and pioneered the northern areas. In this studyI investigate the proportion of first-year singing males in Swedish populations and compare this with data from core areas in Germany and Austria. The proportion of first-year singing males was around 50% in all of the populations, in Sweden as well as in central Europe. However, only a few first-year males return to the Swedish natal area. Perhaps the similar age distribution between the populations indicates an apparent stability in age structure in the Swedish populations. In addition to the territorial males in western Sweden, there are sporadically occurring individuals, which have been attributed to a so-called floating population. Whether the current turnover of young birds in Sweden originates from continental populations, or more nearby areas in Scandinavia, is unknown.